Molecular mechanisms of action of curaxin CBL0137 on breast cancer cells in vitro - V. G. Popova; Е. S. Lylova; A. Yu. Bukina; K. A. Zimin; M. K. Khirin; Е. М. Zhidkova; Е. S. Trapeznikova; M. G. Yakubovskaya; V. P. Maksimova; К. I. Kirsanov (Успехи молекулярной онкологии)
Introduction. Breast cancer (BC) represents a group of malignant neoplasms with various molecular profiles, which are characterized by aberrations in the mechanisms of epigenetic transcription regulation. One of these disruptions associated with a worse prognosis is the overexpression of the BET protein family, responsible for the interaction of transcription factors with histone-rich acetylated regions. Previously, for the multitargeted epigenetically active agent curaxin CBL0137 (CBL), we have shown the ability to inhibit the expression of BRD2, BRD3, BRD4 proteins in HeLa TI cells and BRD3, BRD4 proteins in BC cells.Aim. To analyze the molecular mechanisms of CBL0137 action on BC cells in vitro, including: 1) assessment of cytotoxicity, 2) analysis of the effect on the cell cycle, 3) assessment of the ability to trigger apoptosis, 4) cause DNA damage, and 5) analyze the effect on the expression of genes involved in proliferation, apoptosis and repair processes.Materials and methods. The cytotoxicity of CBL on BC cells (MCF7, MDA-MB-231, SKBR3) was assessed using the MTT assay. The effect of the agent on the cell cycle and activation of apoptosis was analyzed by flow cytometry. Analysis of DNA damage under the action of CBL was performed using the comet assay. Changes in the expression of genes associated with proliferation, repair and apoptosis were evaluated using real-time polymerase chain reaction.Results. The half maximal inhibitory concentration (IC50) on BC cells under the action of CBL0137 were 1 μM at 72-hour exposure, 14–25 μM at 24-hour. Curaxin CBL (0.5 and 1 μM) caused G2/M cell cycle arrest, and also triggered apoptosis in all cell lines. Under the action of 1 μM CBL, an increase in the degree of DNA damage in MCF7 and SKBR3 cells was recorded, and under the action of both concentrations in MDA-MB-231 cells. The gene expression profile involved in proliferation also corresponded to the arrest in the G2/M phase of the cell cycle. Also, under the action of CBL, the activation of p53-dependent repair genes occurred. An increase in the expression of pro-apoptotic and a decrease in anti-apoptotic genes was shown.Conclusion. Curaxin CBL0137 showed differential effects on molecular processes in BC cells. We have identified a cytostatic effect of the compound, confirmed at various molecular levels. The data obtained indicate the ability of CBL0137 to inhibit tumor processes in BC cells, which makes it a potentially interesting agent for combination therapy.